How Do Sex Ratios Affect Marriage and Labor Markets? Evidence from America's Second Generation - Joshua D. Angrist (Institute for the Study of Labor (IZA), 2001)
Sex ratios, i.e., relative numbers of men and women, can affect marriage prospects, labor force participation, and other social and economic variables. But the observed association between sex ratios and social and economic conditions may be confounded by omitted variables and reverse causality. This paper uses variation in immigrant flows as a natural experiment to study the effect of sex ratios on the children and grandchildren of immigrants. The flow of immigrants affected the second generation marriage market because second generation marriages were mostly endogamous, i.e., to members of the same ethnic group. The empirical results suggest that high sex ratios had a large positive effect on the likelihood of female marriage, and a large negative effect on female labor force participation. Perhaps surprisingly, the marriage rates of second generation men appear to be a slightly increasing function of immigrant sex ratios. Higher sex ratios also appear to have raised male earnings and the incomes of parents with young children. The empirical results are broadly consistent with theories where higher sex ratios increase female bargaining power in the marriage market.
Keywords: D13; N32; J12; J13; 330; Household and family models; immigration; family structure; Familienökonomik; Geschlecht; Familie; Ethnische Gruppe; Frauenerwerbstätigkeit; Schätzung; USA